A7.7 Different Genetic Background of Dermatomyositis and Polymyositis in a Single Centre Cohort. (25th February 2013) - Remakova, M; Skoda, M; Svitalkova, T; Faustova, M; Plestilova, L; Betteridge, Z; Mann, H; Vencovsky, J; Krystukova, O; Novota, P
Abstract : Background and Objectives: The idiopathic inflammatory myopathies (IIM) are systemic connective tissue diseases in which autoimmune pathology is responsible for promotion of chronic muscle inflammation and weakness. As in many other autoimmune diseases, the development of IIM is also associated with genes of HLA complex. The aim of this study was to determine the basic relation between alleles of HLA genes and IIM. Materials and Methods: We have performed low to high resolution genotyping to characterise the allelic profiles of HLA-DRB1, -DQB1 and -DQA1 loci in a large group of single centre cohort of patients suffering from IIM (n = 269). The genomic DNA was prepared by standard DNA extraction methods and the HLA typing was done using the commercial LABType® SSO kit (One Lambda, USA). Statistical evaluation of results was done with chi-2 test and Fisher exact test. Autoantibody profiles were analysed with radioactive immunoprecipitation. Results: The frequencies of HLA-DRB1*03:01 and -DRB1*16:01 alleles were increased in IIM patients and the difference reached statistical significance when compared to healthy controls (P < 0.01 for DRB1*03:01; P < 0.05 for DRB1*16:01). Different alleles were associated with dermatomyositis (DM) or polymyositis (PM). The frequency of DRB1*16:01 was significantly higher in DM patients (P < 0.01), whereas the frequency of DRB1*03:01 was higher in patients suffering from PM (P < 0.01), when compared to controls. Presence of HLA-DRB1*03:01 allele was associated with anti-Jo-1, anti-Ro52, or anti-Pm-Scl positivity in all IIM patients (P < 0.05). Interestingly, the DRB1*03:01 allele was also associated with the negativity for anti-p155/140 in our patients (P < 0.01). The DRB1*16:01 allele was associated with negativity of all studied autoantibodies, particularly in subgroup of DM patients (P < 0.05). Conclusions: This study identifies different genetic background between patients with dermatomyositis and polymyositis in a homogenous population of patients from a single centre. Acknowledgement: This work is supported by Internal Grant Agency of Ministry of Health of the Czech Republic NT/12438–4 and NT/13699.